Compositional analysis of locally cultivated carob (Ceratonia siliqua) cultivars and development of nutritional food products for a range of market sectors - Iipumbu, Lukas (Stellenbosch : Stellenbosch University, 2008)
Thesis (Msc Food Sc (Food Science))--Stellenbosch University, 2008.